Translation, Cross-Cultural Adaptation, and Psychometric Testing of Yoruba Version of the EQ-5D Questionnaire in Patients With Musculoskeletal Disorders - Fatoye, Francis; Akinfala, Abiodun Emmanuel; Gebrye, Tadesse; Fatoye, Clara; Ojelade, Titilope Faith; Oyewole, Olufemi Oyeleye; Mbada, Chidozie Emmanuel (Frontiers in Public Health, 2022)
Background The EuroQol-5 Dimension (EQ-5D) is a generic self-administered questionnaire used for the measurement and economic valuation of a wide range of health conditions, which necessitates its existence and adaptation in different languages. Currently, the tool does not exist in any Nigerian language. This study aimed to translate, cross-culturally adapt, and determine the reliability and validity of the Yoruba version of the EQ-5D-5L questionnaire. Methods The International Quality of Life Assessment (IQOLA) project guidelines, involving forward translation, reconciliation and harmonization, backward translation, and reconciliation of problematic items were used in the Yoruba translated version of the EQ-5D-5L (EQ-5D-Yor). A total of 113 and 109 persons with musculoskeletal disorders participated in the validity and 7-day test-retest reliability testing of the EQ-5D-Yor. Convergent and discriminant validity of the EQ-5D-Yor were determined using the Yoruba version of the 12-Item Short-Form Health Survey (SF-12) (SF-12-Y) and Visual Analog Scale (VAS). Data were analyzed using descriptive and inferential statistics of Spearman correlation, Intra-Class Correlation, Cronbach alpha, and multi-trait scaling analysis. Alpha level was set as p < 0.05. Results The construct validity of the EQ-5D-Yor yielded Spearman rho ranging from 0.438 to 1.000, with the EQ-VAS having the highest co-efficient (r = 1.000; p = 0.001). The convergent validity of the EQ-5D-Yor index with scales and domains of the SF-12-Y yielded no significant correlations (p < 0.05), except for the physical functioning scale (r = −0.709, p = 0.001). On the other hand, the divergent validity of the EQ-5D-Yor index with VAS yielded a moderate negative correlation (r = −0.482; p = 0.001). The Intra-class Correlation Coefficient (ICC) and Cronbach's alpha for the test-retest reliability of the EQ-5D-Yor were 1.000 and 0.968. The confirmatory factor analysis showed the factor loadings were poor when including VAS in the model. Conclusion The EQ-5D-Yor has acceptable validity and reliability and can be used as a valid tool among Yoruba speaking population with musculoskeletal disorders.